Deteksi Dini Status Gizi Balita Berdasarkan Berat Badan dan Tinggi Badan - Diana, Sitti Aras; AR, Irmayanti (Yayasan Inspirasi El Burhani, 2025)
Introduction: Measuring growth and detecting development in early childhood is necessary. One of the efforts made to identify nutritional problems in children is by measuring their weight and height. Measuring weight and height can provide an overview of a child's nutritional status, both past and present. Additionally, it allows for the assessment of current physical growth rate and nutritional status by reviewing weight measurement results. Malnutrition has adverse effects both in the short and long term. Children with malnutrition are more susceptible to illness. Children with malnutrition may also experience a decline in intelligence, which could lead to reduced productivity in the future Objective: The objective of this community service activity is to assess the nutritional status of toddlers based on their weight and height at the Al-Fattah Playgroup in Katumbangan Village. Method: The method used in this activity was to conduct a preliminary study. The health examination of toddlers was carried out on Tuesday, July 15, 2025, in Katumbangan Village, Campalagian Subdistrict, Polewali Mandar Regency, targeting toddlers in the Al-Fattah Playgroup. Result: The results of the community service activity showed that out of the 10 toddlers who attended the activity, only 2 were male male and 8 female. The results of the examination revealed the lowest weight of 9.1 kg in a 43-month-old child and a height of 84 cm. Conclusion: The conclusion drawn from the community service activities conducted at the Al-Fattah Playgroup in Katumbangan Village is that it can provide an overview of the nutritional status of infants based on their weight and height. Additionally, the results of this community service activity can serve as input for us collectively regarding the nutritional status of infants and toddlers, as assessed through measurements of weight and height, thereby providing insights for developing future interventions to address the identified issues.